E-Supply Chain Management and Customer Satisfaction in Indonesian E-Commerce - Sarjono, Haryadi; Mahira, Tubagus; Soeratin, Boyke Setiawan (Manunggal Halim Jaya, 2026)
This study examines the impact of Electronic Supply Chain Management (e-SCM) implementation on operational performance and customer satisfaction in Indonesian e-commerce companies. As digital commerce continues to grow rapidly, primarily through platforms such as Shopee and Tokopedia, understanding the effectiveness of supply chain digitization becomes increasingly crucial. The study aims to identify which e-SCM factors contribute most significantly to enhancing company performance and meeting evolving consumer expectations. Using a quantitative approach with 252 respondents, factor analysis identified six critical success factors: market adaptation, inventory control, revenue improvement, remote product monitoring, product quality, and technology utilization. The results demonstrate that effective e-SCM implementation significantly improves process efficiency, cost accuracy, service responsiveness, and product availability, all of which are strongly correlated with customer satisfaction. Furthermore, this research highlights the practical implications for e-commerce companies to overcome challenges such as integration complexity and cybersecurity risks. The findings provide a strategic foundation for firms seeking to enhance their digital supply chains and maintain competitiveness in a rapidly evolving market landscape.